PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA ILLEGAL LOGGING DI WILAYAH HUKUM KABUPATEN KAMPAR BERDASARKAN UNDANG-UNDANG NOMOR 18 TAHUN 2013 TENTANG PENCEGAHAN DAN PEMBERANTASAN PERUSAKAN HUTAN - ERMA LENA; Erdianto '; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Increasing cases of illegal logging, including illegal logging, illegal timber trafficking, encroachment and abuse of authority to permit the use of timber, on a small scale and large scale within an organization. Kampar Regency is one of the areas that have the potential of abundant natural resources, including forests. Basically most people Kampar work as farmers, but the high price of wood and huge market demand for timber, a lot of people who think that the timber business will provide greater profits than on the job as a farmer. so, many people involved in this illegal logging activities. The purpose of this study was to determine law enforcement to the crime of illegal logging In Kampar jurisdiction based on law no. 18 year 2013 concerning the prevention and eradication forest destruction. The results of this study are law enforcement to illegal logging activities in the jurisdiction in Kampar regency Based on Law No. 18 Year 2013 concerning the Prevention and Eradication forest destruction carried out by the police resorts Kampar, investigators civil servants of district forestry services Kampar and national army Indonesia, rangers , the state prosecutor Bangkinang. In enforcing the law, the protection of which is to do with the efforts Pre-emptive, repressive efforts, formed a special team to eradicate illegal logging, because of the high crime of illegal logging in Kampar district.Keywords: Law Enforcement - Illegal Logging